Inovasi Pengabdian Pusat Kesehatan Matematika Sekolah (Puskesmas) dalam Pembelajaran Matematika Berbasis Alun-alun Kota - Supriadi Supriadi (Universitas Mathla'ul Anwar Banten, 2020)
COMMUNITY SERVICE INNOVATION OF THE SCHOOL MATHEMATICS HEALTH CENTER (PUSKESMAS) IN LEARNING MATHEMATICS BASED ON THE TOWN SQUARE. The purpose of this study was to develop an innovation in the school's mathematics health center in mathematics learning through city square-based mathematics learning. Descriptive method is used with subjects in early childhood and elementary school students who are in the location of the school mathematics health center. The instrument used by the researcher itself, data collection techniques using structured interviews, observation and documentation. The data analysis technique used triangulation, data reduction, data presentation and conclusion drawing. The results showed that the media presented at the Puskesmas were all new and they had not yet gotten them in their respective schools. The attitude of students who become happy, like, cheerful in learning mathematics and easy to understand mathematical concepts, and bring out the creativity of early age and elementary school students in learning mathematics. Student concentration also increases because the learning model used uses an individual approach, so that they can focus more on seeing the student learning process. Parents who accompany their children generally feel happy because their children enjoy learning mathematics. Puskesmas activities have an impact on early age and elementary school students to be happy learning mathematics, like learning with mathematics media, cheerful in following math tutoring and enjoy learning mathematics. This program is also highly supported by parents because it is very helpful in the learning process of their children and eases the family's economic burden in education.